2003
DOI: 10.1165/rcmb.2002-0055oc
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNA Induces the Synthesis of Specific Chemokines by Bronchial Epithelial Cells

Abstract: Virus-induced secretion of proinflammatory chemokines (e.g., regulated on activation, normal T cells expressed and secreted [RANTES], interleukin [IL]-8) by airway epithelial cells helps to initiate antiviral responses and airway inflammation by enhancing inflammatory cell recruitment. To define mechanisms for virus-induced chemokine secretion, monolayers of nontransformed bronchial epithelial cells were transfected or incubated with polydeoxyinosinic-deoxycytidylic acid (synthetic double-stranded [ds] RNA), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 26 publications
8
101
2
4
Order By: Relevance
“…Our findings also suggest that to some extent dsRNA and influenza A virus use different signaling mechanisms to induce inflammatory epithelial responses; dsRNA triggers IL-8 secretion via at least the signal-transducing molecules ERK, p38, and PI3K/Akt, whereas RANTES release appears to be mainly dependent on a PI3K/Akt activation. These results are in agreement with recent work showing p38-dependent production of IL-8 but not of RANTES in lung epithelial cells following dsRNA treatment (15). Also, the role of the PI3K-Akt pathway in TLR3-mediated gene induction was robustly supported by Sarkar et al (36) in a very recent study.…”
Section: Tlr3 Signaling and Respiratory Epithelial Cell Activationsupporting
confidence: 92%
“…Our findings also suggest that to some extent dsRNA and influenza A virus use different signaling mechanisms to induce inflammatory epithelial responses; dsRNA triggers IL-8 secretion via at least the signal-transducing molecules ERK, p38, and PI3K/Akt, whereas RANTES release appears to be mainly dependent on a PI3K/Akt activation. These results are in agreement with recent work showing p38-dependent production of IL-8 but not of RANTES in lung epithelial cells following dsRNA treatment (15). Also, the role of the PI3K-Akt pathway in TLR3-mediated gene induction was robustly supported by Sarkar et al (36) in a very recent study.…”
Section: Tlr3 Signaling and Respiratory Epithelial Cell Activationsupporting
confidence: 92%
“…Expression was observed in our mice early in infection and was maximal at day 8 when strong immunoreactivity in epithelial cells lining the airways and in mononuclear cells was obvious. Pulmonary epithelial cells express TLR3 (46,68) and PKR (46,68,69). S100A8 is up-regulated in bronchial epithelial cells by LPS (3) and S100A8/S100A9 is expressed in tracheal epithelial cells from patients with cystic fibrosis (70).…”
Section: Discussionmentioning
confidence: 99%
“…Virus infection and dsRNA have been shown to activate MAPK pathways in different cell types via PKR-dependent and -independent mechanisms and MAPK activation has been implicated in the regulation of inflammatory gene expression (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). We have shown that dsRNA-and EMCV infection stimulates ERK activation and ERK-dependent regulation of IL-1 expression (19, 29 -31).…”
Section: Role Of Mapk In the Regulationmentioning
confidence: 99%